2016
DOI: 10.4103/0970-0358.197235
|View full text |Cite
|
Sign up to set email alerts
|

Awkward defects around the elbow: The radial recurrent artery flap revisited

Abstract: Background:Soft tissue defects on the posterior aspect of the elbow are commonly seen in patients treated with internal fixation for fractures around the elbow joint. An axial flap based on the radial recurrent artery (RRA) is very useful for such defects, especially if a posterior midline arm incision has been taken for skeletal fixation. The aim of this study is to describe the usefulness of RRA flap (based on the RRA) in the management of such defects.Materials and Methods:We present a retrospective analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In cases of olecranon fracture with skin defects, flaps based on the middle collateral artery cannot be used because of damage to the perforators on the posterior side of the elbow 14) . The radial and ulnar artery forearm flaps are not preferred because they sacrifice the major arteries of the forearm 15) .…”
Section: Discussionmentioning
confidence: 99%
“…In cases of olecranon fracture with skin defects, flaps based on the middle collateral artery cannot be used because of damage to the perforators on the posterior side of the elbow 14) . The radial and ulnar artery forearm flaps are not preferred because they sacrifice the major arteries of the forearm 15) .…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical textbooks describe the termination of DBA as a bifurcation into middle and radial collateral arteries, which take part in the peri-articular arterial anastomoses around the elbow (Moore et al, 2017). However, many sources do not mention the posterior radial collateral artery or the anterior radial collateral artery as the terminal branches (Devale et al, 2016) or as alternative names for the branches of the DBA. However, Meirer et al performed an anatomic study carried out on 28 cadaveric arms, to investigate the principal artery of the lateral forearm flap (Meirer et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Their study also included RFF, brachioradialis, pedicled LD, and local perforator flaps as coverage options for posterior elbow that correlates with our case series. The RLA flap can also be based anterior to the lateral epicondyle to include perforators of RRA in the flap base, which minimizes the kink and prevents venous congestion as suggested by Devale et al 6 In a recent review article by Gandolfi et al, 7 the lateral arm flap was the most reported flap in their review due to its obvious advantages.…”
Section: Discussionmentioning
confidence: 99%